2019
DOI: 10.1590/1678-5150-pvb-6305
|View full text |Cite
|
Sign up to set email alerts
|

Herbaspirillum seropedicae as a degrading bacterium of monofluoroacetate: effects of its inoculation in goats by ingesting Amorimia septentrionalis and the concentrations of this compound in plants sprayed with the bacterium

Abstract: Herbaspirillum seropedicae is a nitrogen-fixing bacterium capable of using toxic compounds as a source of carbon. Bacteria with this capacity can be used to make animals resistant to plant poisoning containing monofluoroacetate (MFA), such as Amorimia septentrionalis. The aim of this study was to evaluate if H. seropedicae is efficient in the degradation of MFA present in A. septentrionalis and if the inoculation of this bacterium in goats confers protection to A. septentrionalis intoxication. Two experiments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…In A. septentrionalis samples collected in Pernambuco state, the MFA concentration was practically the same (0.0021%) in the leaves of the adult plant (Albuquerque et al 2014). However, Lopes et al (2019) found 0.00074% MFA in the leaves of A. septentrionalis and Pessoa et al (2019) found 0.16% MFA also in A. septentrionalis leaves; the two plants collected in the same location in Paraíba state. This variation reinforces the claims that plant toxicity varies according to developmental stage (Lee et al 2012, Tokarnia et al 2012, since plants collected in the same region showed variations in toxicity.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…In A. septentrionalis samples collected in Pernambuco state, the MFA concentration was practically the same (0.0021%) in the leaves of the adult plant (Albuquerque et al 2014). However, Lopes et al (2019) found 0.00074% MFA in the leaves of A. septentrionalis and Pessoa et al (2019) found 0.16% MFA also in A. septentrionalis leaves; the two plants collected in the same location in Paraíba state. This variation reinforces the claims that plant toxicity varies according to developmental stage (Lee et al 2012, Tokarnia et al 2012, since plants collected in the same region showed variations in toxicity.…”
Section: Introductionmentioning
confidence: 87%
“…Because H. seropedicae is an endophytic bacterium that is capable of colonizing plants, it was cultivated and later used to spray some plants of the species A. septentrionalis, aiming to evaluate whether there was a reduction in the amount of MFA present in them after spraying. Before spraying, the concentration of MFA found in the plants was 1.21±0.53µg/mg, and a significant reduction in the amount of MFA (0.24±0.05µg/mg) was observed eight days after spraying, suggesting the use of endophytic bacteria, which hydrolyze MFA, as a way to reduce the content of this compound in plants (Pessoa et al 2019). Further studies should be conducted to prove these results and demonstrate the permanence of H. seropedicae in A. septentrionalis plants or in other species containing MFA.…”
Section: Oral Administration Of Mfa-degrading Bacteriamentioning
confidence: 98%